2018
DOI: 10.1186/s12960-018-0289-5
|View full text |Cite
|
Sign up to set email alerts
|

The distance and chance of lifetime geographical movement of physicians in Japan: an analysis using the age-period-cohort model

Abstract: BackgroundThe uneven geographical distribution of physicians in Japan is a result of those physicians electing to work in certain locations. In order to understand this phenomenon, it is necessary to analyze the geographic movement of physicians across the Japanese landscape.MethodsWe obtained individual data on physicians from 1978 to 2012 detailing their attributes, work institutions, and locations. The data are from Japanese governmental sources (the Survey of Physicians, Dentists, and Pharmacists). The tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…7 This reduced between 1974 and 1994, although increased again in later years and by 2006 it was greater than the 1974 levels. 10 While previous research focused on the use of simple cross-tabulation, 9 the Gini coefficient 11 and generalised linear models 12 ; they were often not sufficient to disentangle the complexity of the movements of doctors. To understand the spatial scales and explanatory factors associated with the movements of entrant medical students and junior doctors, in addition to the traditional statistical analyses listed above, we have also employed a new method, the Leslie matrix (usually applied in biology).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…7 This reduced between 1974 and 1994, although increased again in later years and by 2006 it was greater than the 1974 levels. 10 While previous research focused on the use of simple cross-tabulation, 9 the Gini coefficient 11 and generalised linear models 12 ; they were often not sufficient to disentangle the complexity of the movements of doctors. To understand the spatial scales and explanatory factors associated with the movements of entrant medical students and junior doctors, in addition to the traditional statistical analyses listed above, we have also employed a new method, the Leslie matrix (usually applied in biology).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Geotagging has been used for multiple purposes in health care. Some of the main benefits of geotagging are (1) being a better tool for health care data's visualization [6,7], (2) supporting time domain data analysis [8], (3) facilitating cross-analysis of multiple data types [9][10][11], and (4) enabling automatic data analysis [12][13][14].…”
Section: Geotagging In Public Healthmentioning
confidence: 99%
“…It can be employed to evaluate the effectiveness of interventions (eg, evaluating the effectiveness of social distancing for individual neighborhoods in order to provide a more reasonable distribution of resources to assist high-risk populations) [ 15 ], predict trends in population health and health care (eg, using Twitter data to advance Zika virus surveillance) [ 16 ], determine the urgency level of interventions (eg, generating acute ischemic stroke alert or detecting COVID-19 symptoms, testing access, and recovery) [ 17 , 18 ], and identify areas that require further investigation (eg, worsening of the population health due to environmental pollution) [ 19 ]. Researchers of a study conducted in Japan in 2018 obtained geographical movement of physicians to determine the most favorable location and the median distance of geographical movement of female and male groups of health care providers [ 8 ]. The authors concluded that physicians preferred to work in urban areas but there was a higher rate of female physicians who had their first preference of working location as urban areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation